2012
DOI: 10.21913/ijei.v8i1.781
|View full text |Cite
|
Sign up to set email alerts
|

Academic integrity on college campuses

Abstract: A survey of 46 faculty members and 562 undergraduates at a medium-sized Midwestern regional university in May 2011 found that 74% of faculty members believed academic misconduct had recently occurred in their classes; 18% of faculty members have ignored suspected incidents of cheating; and of those faculty members suspecting cheating within their classes, only 18% have reported it to others on campus. Undergraduate students believed all forms of academic misconduct were significantly less serious than faculty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
4
0
3
Order By: Relevance
“…Thus, course instructors could emphasize on the appropriate social norms of using communication technology in the classroom to discourage misconduct behaviors in the classroom. This has also been reiterated in a previous study, where the authors argue that to deter or reduce academic dishonesty, instructors should utilize class time to communicate clearly and explicitly on academic integrity principles and concepts (Williams et al, 2012). For example, while it is appropriate to use an online database to produce a quality research paper, it is unethical to copy and paste materials from the Internet without proper citation.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Thus, course instructors could emphasize on the appropriate social norms of using communication technology in the classroom to discourage misconduct behaviors in the classroom. This has also been reiterated in a previous study, where the authors argue that to deter or reduce academic dishonesty, instructors should utilize class time to communicate clearly and explicitly on academic integrity principles and concepts (Williams et al, 2012). For example, while it is appropriate to use an online database to produce a quality research paper, it is unethical to copy and paste materials from the Internet without proper citation.…”
Section: Discussionmentioning
confidence: 86%
“…Other studies looked at students' attitude towards religion as a predictor; Williams (2018) found that among American college students, religiosity was a significant and negative predictor to propensity to cheat. History with cheating also matters; one study found that those who have cheated will view it as significantly less serious and will be more likely to commit academic dishonesty in the future, compared to those who have not cheated (Williams et al, 2012). Finally, others have examined the effects of environmental factors on academic dishonesty; for instance, peer pressure has a positive relationship with intention to commit academic dishonesty (Winardi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…El CHA-Revisado es una versión actualizada del que se administró en la encuesta previa (Medina-Díaz y Verdejo-Carrión, 2005, 2012a) y el cual era una traducción y adaptación para Puerto Rico del Academic Intregrity Survey (McCabe, 1992). Incorpora cambios en el contenido, producto de los análisis de datos de dicha encuesta y del estudio piloto efectuado en el 2015, así como de la consideración de varias fuentes de referencia (Brimble y Stevenson-Clarke, 2005;Sureda Negre et al, 2009;Williams et al, 2012). Contiene un total 137 ítems que representan 12 componentes vinculados con la deshonestidad académica en universidades en el orden siguiente: (a) Evaluación de factores institucionales (6 ítems); (b) Acciones del profesorado ante la deshonestidad académica (3 ítems); (c) Frecuencia de comportamientos de deshonestidad académica observada en los pares (22 ítems, con 11 acerca de plagio); (d) Gravedad de los comportamientos (22 ítems); (e) Reacciones de estudiantes ante la deshonestidad académica de otros (4 ítems); (f) Importancia de razones para la deshonestidad académica (29 ítems); (g) Frecuencia de comportamientos de deshonestidad académica (51 ítems, con 19 asociados al plagio); (h) Probabilidad de informar incidentes de deshonestidad académica (3 ítems); (i) Tipo de escuela superior (1 ítem); (j) Frecuencia de comportamientos de deshonestidad académica en la escuela superior (10 ítems); (k) Comparación de la deshonestidad académica con la escuela superior (1 ítem) y (l) Información personal y académica (7 ítems).…”
Section: Materiales Y Métodosunclassified
“…Σύμφωνα με τα ευρήματα των ερευνών οι οποίες αξιοποίησαν σενάρια για τη διερεύνηση της εμπλοκής των φοιτητών σε ενέργειες πλαγιαρισμού, ο φοιτητικός πληθυσμός εμφανίζεται να ολισθαίνει (κατ' επιλογή ή όχι) σε αντιδεοντολογικές πρακτικές. Συγκεκριμένα, οι συμμετέχοντες υποστήριξαν την εμπλοκή των ίδιων ή τρίτων στην αντιγραφή (Akbulut et al, 2008• Brimble & Stevenson-Clarke, 2005• Curtis & Popal, 2011• Dick, Sheard, & Markham, 2001• Eret & Ok, 2014• Franklyn-Stokes & Newstead, 1995• Zafarghandi et al, 2012• Harries & Rutter, 2005• Lim & See, 2001• Lin & Wen, 2007• Mazer & Hunt, 2012• Marshall & Garry, 2006• Risquez, O'Dwyer, & Ledwith, 2011• Scanlon & Neumann, 2002• Selwyn, 2008• Sheard & Dick, 2011• Stephens, Young, & Calabrese, 2007• Williams, Tanner, Beard, & Hale, 2012, τη λήψη βοήθειας (Akbulut et al, 2008• Brimble & Stevenson-Clarke, 2005• Curtis & Popal, 2011• Dick et al, 2001• Eret & Ok, 2014• Franklyn-Stokes & Newstead, 1995• Harries & Rutter, 2005• Lim & See, 2001• Lin & Wen, 2007• Mazer & Hunt, 2012• McCabe, 1992• Scanlon & Newmann, 2002• Selwyn, 2008• Sheard & Dick, 2011• Stephens et al, 2007• Williams et al, 2012, την ανεπαρκή παράφραση (Curtis & Popal, 2011…”
Section: η εμπλοκή των φοιτητών σε ενέργειες πλαγιαρισμούunclassified
“…Στο πλαίσιο του συγκεκριμένου ερευνητικού εγχειρήματος εξετάστηκε η πρακτική του πλαγιαρισμού σε μεταπτυχιακούς φοιτητές μέσω του ελέγχου μεταπτυχιακών διατριβών τους και συνεντεύξεων. Η μελέτη των ευρημάτων οδηγεί στη διαπίστωση πως ο πλαγιαρισμός υφίσταται ως πρακτική στην τριτοβάθμια εκπαίδευση κάτι που επιβεβαιώνει προγενέστερα ερευνητικά ευρήματα της διεθνούς βιβλιογραφίας (Akbulut et al, 2008• Andrews et al, 2007• Arce Espinoza & Monge Najera, 2014• Bamford & Sergiou, 2005• Bimble & Stevenson-Clarke, 2005• Chuda et al, 2012• Deckert, 1993• Dick et al, 2001• Eret & Ok, 2014• Franklyn-Stokes & Newstead, 1995• Zafarghandi et al, 2012• Harries & Rutter, 2005• Honny et al, 2010• Leonard et al, 2014• Lim & See, 2001• Lin & Wen, 2007• Marshall & Garry, 2006• Mazer & Hunt, 2012• McCabe, 1992• Oran et al, 2015• Perry, 2010• Pickard, 2006• Risquez et al, 2011• Scanlon & Neuman, 2002• Schrimsher et al, 2011• Selwyn, 2008• Sheard & Dick, 2011• Stephens et al, 2007• Szabo & Underwood, 2004• Wan et al, 2011• Williams et al, 2012. Συνεπώς, απαντάται θετικά το πρώτο ερευνητικό ερώτημα αναφορικά με τη διάδοση πρακτικών πλαγιαρισμού στους φοιτητές.…”
Section: συζήτησηunclassified